Real-Time Joint Personalized Speech Enhancement and Acoustic Echo Cancellation with E3Net - Eskimez, Sefik Emre; Yoshioka, Takuya; Ju, Alex; tang, Min; Parnamaa, Tanel; Wang, Huaming (2022)
Personalized speech enhancement (PSE), a process of estimating a clean target speech signal in real time by leveraging a speaker embedding vector of the target talker, has garnered much attention from the research community due to the recent surge of online meetings across the globe. For practical full duplex communication, PSE models require an acoustic echo cancellation (AEC) capability. In this work, we employ a recently proposed causal end-to-end enhancement network (E3Net) and modify it to obtain a joint PSE-AEC model. We dedicate the early layers to the AEC task while encouraging later layers for personalization by adding a bypass connection from the early layers to the mask prediction layer. This allows us to employ a multi-task learning framework for joint PSE and AEC training. We provide extensive evaluation test scenarios with both simulated and real-world recordings. The results show that our joint model comes close to the expert models for each task and performs significantly better for the combined PSE-AEC scenario.
Submitted to ICASSP 2023